Spinibdella Thor ... - Hernandes, Fabio A.; Skvarla, Michael J.; Fisher, Ray; Dowling, Ashley P. G.; Ochoa, Ronald; Ueckermann, Edward A.; Bauchan, Gary R. (Zenodo, 2016)
Spinibdella Thor Spinibdella Thor, 1930b: 22; 1931a: 39; Atyeo, 1960a: 424; Soliman & Zaher, 1975: 80; Tseng, 1978: 38; Chaudhri et al., 1979: 133; Michocka, 1987: 82. Type-species: Spinibdella reducta Thor, 1930b: 23 by original designation. 121. Spinibdella ampulla Wallace & Mahon, 1972: 568; Millstream, Western Australia, ex green herbaceous, couch grass, Eucalyptus sp. litter. Remarks. Male unknown. Type deposition. ANIC. 122. Spinibdella ankylotricha Omukunda, Theron & Ueckermann, 2012: 9; Limpopo Province, South Africa. Type deposition. NCA. 123. Spinibdella antarctica (Trägårdh, 1907): 24; South Georgia, Grytviken Peninsula, Antarctica, under rocks.— Wallace, 1970: 107. Original designation: Bdella antarctica Trägårdh; Thor, 1931a: 33. Redescription. Wallace (1970). Type deposition. BPBM; USNM, BMNH, ANIC. 124. Spinibdella arenosa Willmann, 1939b: 532; Germany (Wangerooge Island) (Willmann, 1952: 165). Type deposition. ZSM. 125. Spinibdella atyeoi Gupta & Paul, 1985: 14; West Bengal, ... : Published as part of Hernandes, Fabio A., Skvarla, Michael J., Fisher, Ray, Dowling, Ashley P. G., Ochoa, Ronald, Ueckermann, Edward A. & Bauchan, Gary R., 2016, Catalogue of snout mites (Acariformes: Bdellidae) of the world, pp. 1-83 in Zootaxa 4152 (1) on pages 26-30, DOI: 10.11646/zootaxa.4152.1.1, http://zenodo.org/record/261900 ...